Tax Incentives Influence On Corporate Earnings: Evidence From Quoted Manufacturing Companies In Nigeria - Timah, Benson P.; Chukwu, Gospel J. (Archives of Business Research, 2021)
This study examines the influence of tax incentives on corporate earnings of quoted manufacturing companies in Nigeria. The operational dimension of tax incentives adopted are annual allowance, investment allowance, and tax holiday; while the proxy for corporate earnings is earnings per share (EPS), with share capital as a moderating variable. Secondary data for this study are sourced from financial reports of 69 manufacturing firms quoted on the Nigerian Stock Exchange out of a population of 81 in agriculture, conglomerates, consumer goods, healthcare, industrial goods, natural resources, oil and gas operations. Results from data analysis using descriptive statistics and multiple regression, showed that EPS is influenced by the specified operational dimensions, adjusted R2 = 0.62, p < 0.05. Thus, tax incentives influence corporate earnings in quoted manufacturing companies in Nigeria. It is, therefore, recommended that tax incentives should be sustained by the government to enhance corporate revenue and improve investment. Also, investment booster agencies should do more to coordinate activities, disseminate information on available incentives, and assist investors towards optimum capacity utilization to efficiently drive the Nigerian economy to higher heights.